Factors influencing service quality on customer satisfaction at the school sports club in Phu Nhuan district, Ho Chi Minh Cit (Tạp chí khoa học Đào tạo và Huấn luyện Thể thao, 2024)
Factors influencing service quality on customer satisfaction at the school sports club in Phu Nhuan district, Ho Chi Minh Cit